Incorporating digital tool in EFL class to promote students’ participation in reading - RismadewiNi Wayan Monik; Utami IGA Lokita Purnamika (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
Using digital tools in learning offers numerous virtues for teaching and learning activities. The present study aims to investigate the students’ reading experience in the form of their participation in the classroom with the integration of a digital tool, that is, Padlet, in the EFL classroom. This study was conducted in a General English class at UNDIKSHA. General English class is one of the compulsory courses consisting of students across majors of study. The course needs to be taken either in the first or second semester. A mixed method approach was employed where a General English class in UNDIKSHA with a total number of 29 second-semester students participated both in the survey and interviews. The data gathered from the questionnaires, descriptive statistics, and semi-structured interviews were then analyzed quantitatively and qualitatively through interactive model analysis. The results of the questionnaires were analyzed quantitatively by using descriptive statistics, which showed that 6.9% of students’ participation was fairly active, 13.79 were active, and 79.31 were very active. This quantitative data was supported by qualitative analysis from the interview, which found that with the integration of Padlet in the learning, especially in reading class, their motivation to participate has been boosted. The interesting features offered by Padlet have helped them to confidently participate in the classroom, such as sharing ideas in the discussion, answering the questions from the text, and commenting on other students’ posts. Consequently, the findings suggest that incorporating digital tools like Padlet in the EFL classroom fosters a more engaging and interactive learning environment, which could potentially lead to higher overall course satisfaction and retention rates.